1996
DOI: 10.1017/s0033291700034644
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal secretion during major depression in 8- to 16-year-olds, I. Altered diurnal rhythms in salivary cortisol and dehydroepiandrosterone (DHEA) at presentation

Abstract: SynopsisThe association between basal cortisol, dehydroepiandrosterone (DHEA), its sulphate (DHEAS) and major depression was investigated in 8- to 16-year-olds. Eighty-two subjects with major depression, 25 non-depressed psychiatric cases and 40 community controls were systematically assessed for current mental state and hormone levels at 08.00, 12.00 and 20.00 h, assayed from salivary samples collected over a 48 h period. The average mean of the two time points was compared between the three groups. Evening c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(145 citation statements)
references
References 36 publications
5
137
1
1
Order By: Relevance
“…The method suffers from some disadvantages, including lack of compliance (Gutteling et al, 2005). In addition, saliva samples taken after eating or drinking substances with low pH may give falsely high cortisol values (Goodyer et al, 1996). Tobacco use may also interfere with the analysis (Badrick et al, 2007).…”
Section: Limitations and Strengths Of The Methodsmentioning
confidence: 99%
“…The method suffers from some disadvantages, including lack of compliance (Gutteling et al, 2005). In addition, saliva samples taken after eating or drinking substances with low pH may give falsely high cortisol values (Goodyer et al, 1996). Tobacco use may also interfere with the analysis (Badrick et al, 2007).…”
Section: Limitations and Strengths Of The Methodsmentioning
confidence: 99%
“…The cortisol-DHEA has mostly been studied in relation to early-onset depression, where extensive findings point to a higher ratio in clinically depressed adolescents (Goodyer et al, 1998;Goodyer et al, 1996;Goodyer et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The cortisol-DHEA ratio was calculated by dividing cortisol by DHEA secretion at each of the three time points. A high cortisol to DHEA ratio has been suggested to predispose adolescents to adverse psychological health outcomes (Goodyer, Herbert, & Altham, 1998;Goodyer et al, 1996;Goodyer, Herbert, Tamplin, & Altham, 2000). However, it remains unknown whether this is a consequence of high cortisol or low DHEA or both, which highlights the importance of investigating the secretion of both hormones separately, as well as in their ratio form.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A third pediatric study revealed elevations of salivary cortisol, again in the evening hours (08:00 h), in 82 8-to 16-year-old major depressives, in comparison to 65 control cases (Goodyer et al, 1996), while longitudinal follow-up of this cohort revealed that chronic depression was marked by cortisol hypersecretion in the evening (Goodyer et al, 2001a). In the adult literature, a number of HPA axis studies in depressed subjects have yielded conflicting results for a multitude of factors, including method of ascertainment, disorder heterogeneity, and the complex circadian and ultradian periodicity of cortisol (see Posener et al, 2000 for a review).…”
Section: Introductionmentioning
confidence: 94%